2016
DOI: 10.1007/s10549-016-3740-0
|View full text |Cite
|
Sign up to set email alerts
|

High use of complementary and alternative medicine among a large cohort of women with a family history of breast cancer: the Sister Study

Abstract: Purpose Use of complementary and alternative medicine (CAM) is high among U.S. women, yet information is limited on use among women at increased breast cancer risk. We analyzed CAM use among women with a family history of breast cancer. Methods CAM use was analyzed among women enrolled 2003–2009 in the Sister Study cohort. Eligible women were age 35–74, U.S. or Puerto Rican residents, no personal history of breast cancer, and had ≥1 sister with breast cancer. Baseline data on CAM use in the past year was ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Nowadays, breast cancer is evaluated as a curable disease due to the developments in treatment options. This increases life expectancy of patients, so it can be traced as a chronic disease [12].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, breast cancer is evaluated as a curable disease due to the developments in treatment options. This increases life expectancy of patients, so it can be traced as a chronic disease [12].…”
Section: Discussionmentioning
confidence: 99%
“…When patients do not reach the expected treatment goals, they begin to look for alternative methods. In a study conducted in patients with breast cancer undergoing chemotherapy, it was determined that 87% of the patients were using CIC; these practices were patient-applied practices such as dietary supplements (70%), vitamin and mineral supplements (36%), herbal products (42%), other natural products (41%), mind-body based applications (71%), yoga and meditation (24%) and specialist applications such as massage, acupuncture and reiki [14]. When the high usage rate and the distribution of the methods used is considered; it is seen that patients apply methods that may not be safe (such as herbal products) after deciding on their own.…”
Section: Discussionmentioning
confidence: 99%
“…Practices that focus on meditation, relaxation, and spirituality are the common forms of mind-body medicine used by African Americans, especially women. 9 , 12 , 13 A nationwide survey of women with a family history of breast cancer found that African American women were more likely to use CAM practices with meditation or spiritual components, comprising 45.9% of users. 13 Another survey found that AACS are more likely than white cancer survivors to use relaxation techniques, and interest and self-guided use of CAM is high across cancer survivors of various minority backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 12 , 13 A nationwide survey of women with a family history of breast cancer found that African American women were more likely to use CAM practices with meditation or spiritual components, comprising 45.9% of users. 13 Another survey found that AACS are more likely than white cancer survivors to use relaxation techniques, and interest and self-guided use of CAM is high across cancer survivors of various minority backgrounds. 9 Mind-body interventions that focus on stress reduction or psychotherapy may be helpful for female African Americans, who face additional stressors associated with cultural or gendered expectations.…”
Section: Introductionmentioning
confidence: 99%